2019
DOI: 10.1111/ijfs.14107
|View full text |Cite
|
Sign up to set email alerts
|

Optimising chitosan–pectin hydrogel beads containing combined garlic and holy basil essential oils and their application as antimicrobial inhibitor

Abstract: Summary Chitosan–pectin hydrogel beads that trap and release the maximal amount of combined garlic and holy basil essential oils to inhibit food microorganisms were developed based on the central composite design, with chitosan (0.2–0.7% w/v), pectin (3.5–5.5% w/v) and calcium chloride (CaCl2) (5.0–20.0% w/v) contents. The optimal bead consisted of 0.3–0.6% w/v chitosan, 3.9–5.1% w/v pectin and 8.0–17.0% w/v CaCl2, which had a high encapsulation efficiency (62.16–79.06%) and high cumulative release efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 58 publications
0
25
0
1
Order By: Relevance
“…Pectins are widely used in the food industry as emulsifier and gelling agents. The ability of pectins to form gels under specific conditions has been used to obtain aerogels [86,106], hydrogels [87,107] or oleogels [88,108]. In particular, hydrogels are the most popular gel compositions used in food packaging, since they are able to absorb large amounts of water or other biological fluids inside their structure.…”
Section: Emulsions and Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pectins are widely used in the food industry as emulsifier and gelling agents. The ability of pectins to form gels under specific conditions has been used to obtain aerogels [86,106], hydrogels [87,107] or oleogels [88,108]. In particular, hydrogels are the most popular gel compositions used in food packaging, since they are able to absorb large amounts of water or other biological fluids inside their structure.…”
Section: Emulsions and Gelsmentioning
confidence: 99%
“…In particular, hydrogels are the most popular gel compositions used in food packaging, since they are able to absorb large amounts of water or other biological fluids inside their structure. For example, Torpol et al studied the encapsulation of two different antimicrobial compounds: garlic and holy basil essential oils in chitosan-pectin hydrogel beads [87]. The entrapment of essential oils in the matrix structure was successful and it showed antimicrobial capacity against Bacillus cereus, Clostridium perfringens, Escherichia coli, Pseudomonas fluorescens, Listeria monocytogenes and Staphylococcus aureus, but not against Lactobacillus plantarum and Salmonella Typhimurium.…”
Section: Emulsions and Gelsmentioning
confidence: 99%
“…They demonstrated that combinations of rosemary and clove EOs indicated synergistic or additive effects against the test bacteria and fungi strains, except Aspergillus niger . Similarly, Torpol, Sriwattana, Sangsuwan, Wiriyacharee, and Prinyawiwatkul (2019) demonstrated that chitosan–pectin hydrogel beads containing combined garlic and holy basil essential oils effectively inhibited Staphylococcus aureus , Clostridium perfringens , Bacillus cereus , Escherichia coli , Listeria monocytogenes, and Pseudomonas fluorescens but did not affect Salmonella typhimurium and Lactobacillus plantarum . Furthermore, Lv, Liang, Yuan, and Li (2011) worked on EO combinations and four kinds of EO mixtures were recommended against food‐related microorganisms by synergism testing including oregano, perilla, basil, and bergamot.…”
Section: Resultsmentioning
confidence: 98%
“…Torpol et al. (2019) developed chitosan–pectin hydrogel bead incorporated with garlic and holy basil EOs to inhibit food microorganisms and proved its antimicrobial activity against B. cereus , Clostridium perfringens , E. coli , Pseudomonas fluorescens , L. monocytogenes, and S. aureus . The main compounds of O. majorana EO used in the current study were carvacrol, thymol, trans‐caryophyllene, and cymene (Partovi et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may be attributed to the main constituents of marjoram EO in the aforementioned study (terpinen-4-ol, cis-sabinene hydrate, γ-terpinene, α terpinene, and sabinene) which had high aqueous solubility and as a result lower antimicrobial activity. Torpol et al (2019) developed chitosan-pectin hydrogel bead incorporated with gar- The main compounds of O. majorana EO used in the current study were carvacrol, thymol, trans-caryophyllene, and cymene (Partovi et al, 2018). Carvacrol and thymol antimicrobial properties have been proved in the food matrix (Barbosa et al, 2015;D'Amato et al, 2016).…”
Section: Microbiological Analysis and Tvb-n Values Of Ground Beefmentioning
confidence: 99%